Problems and prospects of cultivation of indigenous rice landraces of Uttar Dinajpur, West Bengal, India with special reference to Tulaipanji - Biswas, Ishita; Mitra, Debasis; Mitra, Debanjan; Chakraborty, Abhinobo; Basak, Goutam; Bhuimali, Anil; Das Mohapatra, Pradeep K. (ORYZA-An International Journal of Rice, 2021)
The district Uttar Dinajpur of West Bengal is bestowed with very fertile soil, which helps to grow paddy and other agricultural crops. Cultivation of indigenous rice has been practiced by farmers since ancient times. Indigenous rice has several socio-economic, ecological and genetical aspects but the major problem lies in their comparatively low output. The diversity of indigenous rice landraces has been drastically reduced due to the introduction of high yielding varieties (HYVs). Through extensive survey it has been found that about 74 indigenous rice land races were available in different blocks of the district, but among them only about 20 varieties are now in farmers' hand while more than 70% of them are not cultivated in practical field. In India, the indigenous aromatic rice landrace Tulaipanji (GI 530) is only grown in Raiganj sub-division of Uttar Dinajpur and small pockets of Dakshin Dinajpur district of West Bengal. Due to its aroma and quality this rice could make the position in global market through proper marketing. A phylogenetic study of the rice landraces has been performed and observed that only three of them i.e., Tulaipanji, Radhunipagal and Gobindavog are closely related to each other, which also has the close lineage with the Asian wild-rice (Oryza rufipogon). Today's society demands the interaction and incorporation of scientific technology for the upliftment of indigenous rice landrace sustainable cultivation. Really it has the immense scope and prospects, which ultimately save the human life from notorious diseases.